Purifikasi Akal dan Nafsu Menuju Hidup Bermartabat (Teori Etika dan Moral JJ Rousseau dan lbn Miskawaih) - Mansur, Amril (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2005)
This study attempts to discuss the existence of logic and passion in deciding moral values and to what extent ethical thought of Ibu Miskawaih dan JJ Rousseau, can give contribution to the modern life. It is a library research with descriptive and critical comparative analysis. The results of this study show that both lbu Miskawaih and JJ Rousseau achtowledge thefunction of logic (reasoning) in creating moral behavior. Human beings need passion for their perfection in life. The dialectic between brain and passion signrficantly determines the quality of the produced good deeds and morality. The results of this study recommend that brain and passion are not the only things determining morality but there are other elements, which is what the heart says, the aworeness andfreedom. This study needs to befollowed up due to the huge problem of ethics.